Initiating Long-acting Injectable Naltrexone: Procedure for a Second Attempt After a First Attempt Fails. Issue 5 (14th September 2022) - Shulman, Matisyahu; Hu, Mei Chen; Nunes, Edward V.; Bisaga, Adam
Abstract : Background and Objective: Many patients are unable to initiate long-acting injectable naltrexone (XR-NTX) on a first attempt, due to the prerequisite abstinence and withdrawal from opioids. Methods: Thirty patients who were unable to initiate XR-NTX were recruited to receive buprenorphine for 1 week, followed by a 3-week buprenorphine taper, and an ascending titration of oral naltrexone before XR-NTX injection. Results: Eight (27%) initiated XR-NTX, 7 (23%) transitioned to buprenorphine maintenance treatment and 15 (50%) were lost to follow up. Conclusion and Scientific Significance: A second attempt at XR- NTX initiation using buprenorphine stabilization and cross taper may be a reasonable approach for some patients.